(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The SafeWAVE project addressed non-technological barriers in the offshore renewable energy (ORE) sector, focusing on environmental impact assessment, consenting processes, marine spatial planning, and public engagement. A priority topic of environmental research was the assessment of fish communities around ORE installations. This study compares two approaches: (i) traditional trawling at Aguçadoura (Portugal) to establish baseline fish community data, and (ii) innovative techniques using autonomous unmanned systems (WBAT and ITSASDRONE) at BiMEP (Spain) to monitor the fish communities and assess ORE impacts. Trawling provided robust species composition and abundance data but lacked behavioural insights. It also had high costs, labour intensity, and potential ecosystem disturbance. Innovative techniques, in contrast, offered scalable, minimally invasive alternatives with high-resolution spatial and temporal data but were limited in describing species composition. The findings highlight the need for an integrated monitoring approach that combines traditional and emerging technologies. Recommendations include technology standardization, improved stakeholder collaboration, and multi-method strategies for comprehensive fish community assessments. These advancements will strengthen environmental monitoring protocols and support the sustainable expansion of ORE.